Local passivation of metals at grain boundaries: In situ scanning tunneling microscopy study on copper. (October 2016) - Chen, Hu; Bettayeb, Mohamed; Maurice, Vincent; Klein, Lorena H.; Lapeire, Linsey; Verbeken, Kim; Terryn, Herman; Marcus, Philippe
Highlights: Local passivation at metal grain boundaries was studied in situ on copper. Metallic and passivated surfaces were analysed with scanning tunneling microscopy. The Cu(I) passive film is found thicker at grain boundaries than on grains. A thicker passive film is formed at random grain boundaries than at coherent twins. No metal is preferentially consumed by transient dissolution at grain boundaries. Abstract: Passivation at grain boundaries was investigated on copper with Electrochemical Scanning Tunneling Microscopy. The depth in intergranular regions was measured and its variation was discussed in terms of dissolution or passive film formation. The Cu(I) passive film is found to be thicker at grain boundaries than on grains but with a similar stoichiometry. A thicker Cu(I) passive film is observed at random grain boundaries than at coherent twins. No metal is preferentially consumed at grain boundaries by transient dissolution during Cu(I) passivation. Comprehensive comparison with Cu(I)/Cu(II) passivation shows that transient dissolution is a revelator of the grain boundary-type dependent behavior.